The efficacy and safety of acupuncture in women with primary dysmenorrhea: A systematic review and meta-analysis. Issue 23 (June 2018) - Woo, Hye Lin; Ji, Hae Ri; Pak, Yeon Kyoung; Lee, Hojung; Heo, Su Jeong; Lee, Jin Moo; Park, Kyoung Sun
Abstract: Background: This systematic review aimed to evaluate the current evidence regarding the efficacy and safety of acupuncture on primary dysmenorrhea. Methods: Ten electronic databases were searched for relevant articles published before December 2017. This study included randomized controlled trials (RCTs) of women with primary dysmenorrhea; these RCTs compared acupuncture to no treatment, placebo, or medications, and measured menstrual pain intensity and its associated symptoms. Three independent reviewers participated in data extraction and assessment. The risk of bias in each article was assessed, and a meta-analysis was conducted according to the types of acupuncture. The results were expressed as mean difference (MD) or standardized mean difference (SMD) with 95% confidence intervals (CIs). Results: This review included 60 RCTs; the meta-analysis included 49 RCTs. Most studies showed a low or unclear risk of bias. We found that compared to no treatment, manual acupuncture (MA) (SMD = −1.59, 95% CI [−2.12, −1.06]) and electro-acupuncture (EA) was more effective at reducing menstrual pain, and compared to nonsteroidal anti-inflammatory drugs (NSAIDs), MA (SMD = −0.63, 95% CI [−0.88, −0.37]) and warm acupuncture (WA) (SMD = −1.12, 95% CI [−1.81, −0.43]) were more effective at reducing menstrual pain. Some studies showed that the efficacy of acupuncture was maintained after a short-term follow-up. Conclusion: The results of this study suggest that acupuncture might reduce menstrual pain and associated symptoms more effectively compared to no treatment or NSAIDs, and the efficacy could be maintained during a short-term follow-up period. Despite limitations due to the low quality and methodological restrictions of the included studies, acupuncture might be used as an effective and safe treatment for females with primary dysmenorrhea. Abstract : Supplemental Digital Content is available in the text